Expanding Kazakhstan’s agricultural exports: Opportunities and Challenge - Жайшылык, Н.; Фанг, Сун (Journal of Economic Research & Business Administration, 2017)
This paper considers of opportunities expanding Kazakhstan’s agricultural export. This is due to the fact that Kazakhstan is now widely regarded as a key player on world agricultural markets, with considerable export potential in the wheat, beef and dairy sectors. This analysis offers new insights into the constraints that hamper further economic growth and provides an assessment of the government’s agricultural development strategy. Along with, in this paper discusses the challenges of expanding Kazakhstan’s agricultural exports. Meanwhile, to being essential for food security and social stability, agriculture is also an essential part of the government’s strategy to diversify the economy and reduce its dependence on mineral and fossil fuel resources. Agriculture has consistently been identified as a priority sector in government programs for diversification, export promotion and the attraction of foreign direct investment.